MANTRA TRADISI JALUR KABUPATEN KUANTAN SINGINGI - Ummu Nisa; Syafrial Syafrial; Elmustian Elmustian (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This research aims to explain the processions and mantras contained in the jalur tradition. Pacu jalur not only involve physical elements, but also mystical things. The handler is the person who is trusted in the procession of jalur tradition. The role of the handler is clearly seen from the search for wood to the point when the track is finished. Therefore, it is necessary to study the ethnographic approach and function of the mantra found in the jalur tradition. This study uses qualitative methods. This method is considered appropriate because the data required are all words or explanations. Data collection techniques used were observation, interviews, and documentation. Information relating to this study was obtained from key informants, namely: jalur handler. The results of the study found a procession of pathway traditions that used crunches and spells. The persistence of things that are mystical in the jalur tradition adition because people believe that it has the power to be able to protect and influence in winning the race. Key Words: Jalur Tradition, Handler, Spell, and Kuantan Singingi.